The Accompaniment in "Unaccompanied" Bach : Interpreting the Sonatas and Partitas for Violin - Ritchie, Stanley (Book collections on Project MUSE., 2016)
Known around the world for his advocacy of early historical performance and as a skilled violin performer and pedagogue, Stanley Ritchie has developed a technical guide to the interpretation and performance of J.S. Bach's enigmatic sonatas and partitas for solo violin. Unlike typical Baroque compositions, Bach's six solos are uniquely free of accompaniment. To add depth and texture to the pieces, Bach incorporated various techniques to bring out a multitude of voices from four strings and one bow, including arpeggios across strings, multiple stopping, opposing tonal ranges, and deft bowing. Published in 1802, over 80 years after its completion in 1720, Bach's manuscript is without expression marks, leaving the performer to freely interpret the dynamics, fingering, bowings, and articulations. Marshaling a lifetime of experience, Stanley Ritchie provides violinists with deep insights into the interpretation and technicalities at the heart of these challenging pieces.